Composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three parts and its preparation method

By developing a composite antioxidant ceramic glaze containing components such as quartz powder, potassium feldspar, glass powder, etc., and using specific preparation methods, the problem of oxidation and carbon loss of metallurgical continuous casting is solved, which significantly improves the service life of the three major continuous castings and provides high-temperature protection.

CN112125522BActive Publication Date: 2025-03-11WUXI NANFANG REFRACTORIES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010329119.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-23
Publication Date
2025-03-11
Estimated Expiration
2040-04-23

AI Technical Summary

Technical Problem

The existing metallurgical continuous casting medium-packing refractory materials lose carbon oxidation at high temperatures, resulting in the shortening of the life of the three continuous casting parts (long water outlets, plug rods, and immersion water outlets). The inorganic coatings used cannot generate liquid phases and glass phases, and cannot effectively protect the refractory materials.

Method used

It provides a three-piece composite antioxidant and erosion-resistant ceramic glaze containing quartz powder, potassium feldspar, glass powder and other components, and adopts specific preparation methods, including ball milling, wet ball milling, screening, iron removal and decomposition steps to form a glaze with good antioxidant, wear resistance and adhesion effects.

Benefits of technology

This glaze can effectively increase the service life of the three continuous casting parts, provide high temperature protection, prevent oxidation and corrosion, and is simple to use and has significant results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000009439830000011
    Figure GHA0000009439830000011
  • Figure GHA0000009439830000071
    Figure GHA0000009439830000071
  • Figure GHA0000009439830000081
    Figure GHA0000009439830000081
Patent Text Reader

Abstract

The invention discloses a composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three large pieces. The glaze comprises the following components in terms of weight percentage: 18% to 20% of quartz powder, 21% to 27% of potassium feldspar, 5% to 8% of Suzhou soil, 0% to 3% of barium carbonate, 8% to 12% of glass powder, 8% to 10% of pyrophyllite, 0% to 3% of zinc oxide, 5% to 7% of borax, 0% to 2% of magnesia, 0% to 3% of chromium oxide green, 0% to 3% of cobalt blue powder, 0% to 3% of iron red powder, 0% to 5% of diopside, 0% to 15% of frit, 0% to 5% of wollastonite, 0% to 2% of lead oxide, 0% to 5% of calcite, 0% to 0.2% of sodium humate, 0% to 20% of binder, 0% to 8% of silica sol, 0% to 2% of styrene-acrylic emulsion and 20% to 25% of water. The invention has the beneficial effects of being environmentally friendly, having good oxidation resistance, wear resistance, good adhesion effect, and being able to effectively increase the service life of three major parts of the sprayed product, including continuous casting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic non-metallic materials for metallurgical continuous casting, and more specifically to a composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three major parts and a preparation method thereof. Background Art

[0002] As the use conditions of refractory materials in the metallurgical industry are harsh, users have higher and higher requirements for quality and life, especially; the refractory materials of the continuous casting tundish are contracted by tons of steel, and only refractory materials with a long life have a good profit margin. For example, the three major parts of continuous casting (long nozzle, stopper rod, immersed nozzle) contain about 15% C in the brick. During the baking process of the new ladle, in the presence of oxygen and high temperature, when the temperature is greater than 480℃, C and oxygen undergo redox reactions to generate CO2 and lose carbon. Moreover, the higher the temperature, the faster the oxidation rate, resulting in the three major parts of the tundish continuous casting (long nozzle, stopper rod, immersed nozzle) The life is not extended and the tundish is taken offline early. According to the baking curve requirements of the tundish of most steel mills:

[0003]

[0004] At present, a layer of glaze is sprayed on the surface of the three major parts of continuous casting (long shroud, stopper rod and immersion shroud) in China to achieve the purpose of protecting the refractory brick body. After many investigations, most domestic manufacturers use inorganic binders to formulate, which is actually an inorganic coating. It cannot generate liquid and glass phases to form glaze at high temperatures and cannot protect the three major parts of refractory continuous casting (long shroud, stopper rod and immersion shroud). Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a composite antioxidant and corrosion-resistant ceramic glaze for continuously cast three major parts, which is environmentally friendly, has good antioxidant properties, is wear-resistant, has good adhesion effect, and can effectively increase the service life of the three major parts of the continuously cast products being sprayed, and a preparation method thereof.

[0006] According to one aspect of the present invention, a composite antioxidant and erosion-resistant ceramic glaze for continuous casting of three large pieces is provided, which comprises the following components by weight percentage: 18% to 20% quartz powder, 21% to 27% potassium feldspar, 5% to 8% Suzhou soil, 0% to 3% barium carbonate, 8% to 12% glass powder, 8% to 10% pyrophyllite, 0% to 3% zinc oxide, 5% to 7% borax, 0% to 2% magnesia, 0% to 3% chromium oxide green, 0% to 3% cobalt blue powder, 0% to 3% iron red powder, 0% to 5% diopside, 0% to 15% frit, 0% to 5% wollastonite, 0% to 2% lead oxide, 0% to 5% calcite, and in addition, 0% to 0.2% sodium humate, 0% to 20% binder, 0% to 8% silica sol, 0% to 2% styrene acrylic emulsion and 20% to 25% water are added.

[0007] 4. In some embodiments, the quartz powder has a SiO2 content of 99-99.5% and a Fe2O3 content of ≤0.005% by weight;

[0008] Magnesia: MgO content ≥ 97%, SiO2 content ≤ 0.6%, CaO content ≤ 1.2%, Fe2O3 content ≤ 0.6%;

[0009] Glass powder: Physical properties, appearance of white powder, whiteness: ≥94: specific gravity: 2.7g / ml, oil absorption: 28±2.5g / 100g, Mohs hardness: 7.8, chemical composition: SiO2 content 73%, Al2O3 content 0.8%, CaO content 8%, MgO content 3.%, K2O content 1.8%, Na2O content 12.%;

[0010] Pyrophyllite: Al2O3 content ≥16%, SiO2 content ≤75%, Fe2O3 content ≤1.0%;

[0011] Potash feldspar: SiO2 content is 64%, Al2O3 content is 18%, and K2O content is 16%.

[0012] In some embodiments, the particle size distribution of the components is: the quartz powder, potassium feldspar, glass powder, pyrophyllite, magnesia, and calcite are ≥ 325 mesh;

[0013] Suzhou clay, barium carbonate, zinc oxide, borax, lead oxide, cobalt blue powder specifications ≥ 200 mesh;

[0014] The frit is granular;

[0015] Sodium humate, styrene acrylic emulsion, silica sol and water glass are all liquids.

[0016] In some embodiments, the binder is one or a mixture of silica sol, water glass or styrene acrylic emulsion.

[0017] In some embodiments, the binder is a mixture of silica sol, water glass and styrene acrylic emulsion, and the amount of water glass added is 18% to 23%.

[0018] According to one aspect of the present invention, a method for preparing a composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three major parts is provided, which is prepared by the following steps:

[0019] A. Ingredients: 18% quartz powder, 22% potassium feldspar, 6% Suzhou soil, 3% barium carbonate, 8% glass powder, 8% pyrophyllite, 3% zinc oxide, 5% borax, 2% magnesia, 3% cobalt blue powder, 15% frit, 2% lead oxide, 5% calcite, and 0.02% sodium humate, 20% water glass, 8% silica sol, 2% styrene acrylic emulsion and 25% water. After mixing the components, weigh the required weight of various powders based on dry materials, mix them and put them into the rapid ball mill barrel, run for 2 hours, and mix them evenly;

[0020] B. Wet ball milling: Add liquid additive sodium humate and liquid binder styrene acrylic emulsion, silica sol and water glass into the barrel of the fast ball mill filled with powder, and mix and stir by ball milling. The glaze particles are finely ground by the impact and friction of the corundum balls in the ball mill. The ball milling stirring time is 10 to 18 hours, until the specification of the glaze slurry reaches 0.02% to 0.05% of the 350 mesh residue;

[0021] C. Screening: Use a coarse mesh screen to separate the ball material;

[0022] D. Iron removal: Use a magnetic bar to stir the slurry barrel to remove iron impurities, repeat several times;

[0023] E. Aging: The glaze ages for 3 to 5 days;

[0024] F. The glaze is now prepared and will be stored in the warehouse for future use.

[0025] The composite anti-oxidation and erosion-resistant ceramic glaze for the three major parts of continuous casting (long nozzle, stopper rod, immersion nozzle) of the present invention is pollution-free to the environment, has good anti-oxidation and wear resistance, has good adhesion effect, no cracks, no pinholes, no bubbles, no peeling, no sagging, and the protective layer is smooth and shiny after high-temperature baking. It can effectively increase the service life of the three major parts of continuous casting (long nozzle, stopper rod, immersion nozzle) of the immersed and coated product, and the ceramic glaze is simple to use and has significant effects.

[0026] It also has the functions of high temperature erosion resistance, wear resistance, oxidation resistance and slag resistance in all C-containing refractory products such as blast furnace ironmaking refractory containing asphalt C and continuous casting three-piece refractory containing graphite C. At the same time, it has the function of preventing coking in the high-temperature furnace of the coking plant. Due to the increasing pressure of environmental protection, to prevent the leakage of waste gas, the high concentration of this glaze can be applied to the gap of the furnace door to prevent the leakage of waste gas and pollute the environment and meet the environmental protection requirements. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific implementation modes.

[0028] The composite antioxidant and corrosion-resistant ceramic glaze for continuous casting of three large pieces comprises the following components by weight percentage: quartz powder 18% to 20%, potassium feldspar 21% to 27%, Suzhou soil 5% to 8%, barium carbonate 0% to 3%, glass powder 8% to 12%, pyrophyllite 8% to 10%, zinc oxide 0% to 3%, borax 5% to 7%, magnesia 0% to 2%, chromium oxide green 0% to 3%, cobalt blue powder 0% to 3%, iron red powder 0% to 3%, diopside 0% to 5%, frit 0% to 15%, wollastonite 0% to 5%, lead oxide 0% to 2%, calcite 0% to 5%, sodium humate 0% to 0.2%, binder 0% to 20%, silica sol 0% to 8%, styrene acrylic emulsion 0% to 2% and water 20% to 25%.

[0029] The role of calcite in glaze body:

[0030] 1. It acts as a lean material in the green body before decomposition.

[0031] 2. After heating and decomposition, it acts as a flux, reacting with the clay and quartz in the body at a lower temperature, shortening the firing time.

[0032] 3. Increase the thermal expansion coefficient of the body, which is beneficial to the bonding of the body and glaze.

[0033] 4. Increase the amount of the intermediate layer between body and glaze.

[0034] 5. Reduce the firing shrinkage of the product, which is beneficial to improve the regularity of the product.

[0035] 6. It can bleach the green body and improve the whiteness of the product.

[0036] 7. Reduce the moisture absorption and expansion of the blank.

[0037] The amount of calcite used in the blank is generally about 6%. When used in combination with other raw materials, the amount can be appropriately increased or decreased.

[0038] The role of wollastonite in glaze body:

[0039] 1. Wollastonite needle-shaped crystals provide a channel for rapid water discharge, which can accelerate the drying speed and improve the raw strength and post-burning strength of the product.

[0040] 2. It has small drying shrinkage, does not contain water, and does not produce gas during the firing process. It is extremely beneficial to improving the structure of the green body and improving the quality of the glaze. It is also suitable for one-time firing.

[0041] 3. The content of alkaline earth metal oxides is low, the wet expansion coefficient of the green body is small, and it is not easy to crack.

[0042] 4. The thermal expansion of the blank is linearly related to the temperature, which is particularly suitable for fast firing.

[0043] 5. Wollastonite minerals contain a small amount of garnet and diopside, which can act as a mineralizer during the firing process, promote the reaction between wollastonite and other materials, and form a low-viscosity glass phase to bond the billet particles together, improve the billet strength, and promote the development of the billet intermediate layer.

[0044] 6. The wollastonite blank has a small shrinkage rate during firing and is not easily deformed during the firing process.

[0045] The properties of wollastonite bodies depend on the degree of reaction during firing to form anorthite and cristobalite, as well as the properties of residual wollastonite.

[0046] The amount of wollastonite used in the blank can range from 5% to 30%. If the purpose is to improve the blank, 6% can be added; if wollastonite is used as the main raw material, the amount can be as high as 30%.

[0047] The role of diopside in glaze body:

[0048] 1. Reduce the firing temperature. Adding diopside to the glaze body can reduce the firing temperature by 150-200℃.

[0049] 2. It is conducive to the rapid drying of the green body. Since diopside is a needle-shaped or columnar crystal, it provides a channel for the rapid removal of moisture from the green body. In addition, its thermal expansion coefficient is small, so it is conducive to the rapid drying of the green body.

[0050] 3. It can shorten the firing cycle and perform rapid firing. The rapid firing of diopside is mainly reflected in the fact that the green body can quickly complete the three stages of preheating, firing and cooling.

[0051] During the drying and heating stage, diopside has the following characteristics that facilitate rapid heating:

[0052] (1) Diopside itself does not contain organic matter, crystal water, or adsorbed water.

[0053] (2) From the differential thermal analysis curve, it can be seen that diopside does not undergo rapid phase transition below 1200℃.

[0054] (3) From the thermal expansion curve, we can see that the thermal expansion of diopside is relatively uniform from room temperature to 1000℃ (linear expansion). The expansion amount does not change much from 1000 to 1100℃.

[0055] During the firing stage, the diopside glazed tile body produces calcium feldspar, cristobalite and a small amount of mullite. The exothermic effect produced is much smaller than the exothermic effect of mullite, cordierite and cristobalite formed at high temperature of ordinary glazed tile bodies, so it can be fired quickly.

[0056] 4. Reduce firing shrinkage.

[0057] 5. Improve the mechanical strength of the glaze. Diopside glaze is mainly composed of diopside and quartz as aggregates, plus calcium feldspar, cristobalite and a small amount of mullite and glass inclusions. These minerals are arranged in a network with long columnar and needle-shaped crystals, which are solidified by other small crystals and glass around, so they have high mechanical strength.

[0058] 6. Good thermal stability. The amount of diopside added to the glaze body should be less than 50%. The bisque firing temperature should be appropriate, generally controlled below 1100℃.

[0059] The role of glass powder in glaze body:

[0060] Glass powder is a highly transparent powder that is easy to polish and scratch-resistant. It has small particle size, good dispersibility, high transparency and good anti-settling effect. After multiple surface improvements, it has good affinity and strong steric hindrance. It can be easily dispersed in the paint and can increase the fullness of the glaze after film formation. The resulting crystal transparent glaze not only maintains the transparency of the varnish, but also provides good polishability.

[0061] The role of silicon oxide in glaze body:

[0062] The basic component of glaze, the commonly used silicon dioxide is quartz, which plays the role of increasing the melting temperature in the glaze, expanding the melting temperature range, reducing the fluidity of the glaze, increasing the high-temperature viscosity of the glaze, reducing the thermal expansion coefficient, and increasing the hardness of the glaze.

[0063] The role of borax in glaze body:

[0064] Borax is a water-soluble borate. When used in glaze, it is best to make it into a frit before use. Borax is heated to 60℃ and dehydrated into borax pentahydrate. At 90℃, it becomes borax dihydrate. At 130℃, it becomes borax monohydrate. At 350-460℃, it loses all the crystal water and becomes anhydrous borax. It melts into a transparent glass-like substance when heated to 741℃. Molten borax easily dissolves various heavy metal oxides. It reacts with copper oxide to form a blue color, with chromium oxide to form a green color, with manganese oxide to form a purple color, and with iron oxide to form a brown color. Because borax has a good effect in fluxing and coloring, it has become one of the main raw materials for glaze.

[0065] The role of zinc oxide in glaze body:

[0066] Zinc oxide can be obtained by direct heating and oxidation of metallic zinc. It is a white powder with a molecular weight of 81.4 and a specific gravity of 5.6. In glaze, zinc oxide has the advantages of helping melting, reducing expansion, preventing cracking, increasing gloss and whiteness, widening the firing temperature range, and preventing eggshell surface. When ZnO replaces part of CaO, it can prevent the volatilization of lead, because when there is too much CaO, it will rob SiO2 and leave volatile PbO. Calcined zinc oxide has a high density and good glaze slurry fluidity, which reduces the shrinkage of the glaze before firing and prevents glaze shrinkage.

[0067] The role of magnesium oxide in glaze body:

[0068] At high temperatures, it can increase the melting temperature range of the glaze, increase the whiteness of the glaze during flame firing, and prevent the glaze from cracking. The calcium in artistic glaze is also taken from limestone, etc. The magnesium oxide component is taken from fossils, dolomite, etc.

[0069] The role of lead oxide in glaze body:

[0070] Common lead oxides include red lead (Pb3O4), lead oxide (PbO) and lead dioxide (PbO2). Red lead is the most commonly used raw material for ceramic glazes. Its structure is as follows: Pb3O4 decomposes O2 to become PbO at around 500°C. If we use lead oxide as the raw material, when the glaze is to be fired, it is easy to reduce to gray and black metallic lead in the reducing atmosphere of the kiln with insufficient oxygen. 2PbO+C→2Pb+CO2 is the most commonly used flux in glazes and the main raw material for low-temperature glazes. Because lead is toxic, it is not suitable for toys, tableware, and daily-use porcelain.

[0071] Composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three major parts, calculated by weight percentage, quartz powder:

[0072] SiO2 content 99-99.5%, Fe2O3 content ≤ 0.005%;

[0073] Magnesia: MgO content ≥ 97%, SiO2 content ≤ 0.6%, CaO content ≤ 1.2%, Fe2O3 content ≤ 0.6%;

[0074] Glass powder: Physical properties, appearance of white powder, whiteness: ≥94: specific gravity: 2.7g / ml, oil absorption: 28±2.5g / 100g, Mohs hardness: 7.8, chemical composition: SiO2 content 73%, Al2O3 content 0.8%, CaO content 8%, MgO content about 3.%, K2O content 1.8%, Na2O content 12.%;

[0075] Pyrophyllite: Al2O3 content ≥16%, SiO2 content ≤75%, Fe2O3 content ≤1.0%;

[0076] Potash feldspar: SiO2 content is 64%, Al2O3 content is 18%, and K2O content is 16%.

[0077] The particle size distribution of the components is as follows: the quartz powder, potassium feldspar, glass powder, pyrophyllite, magnesia, chromium oxide green, diopside, calcite, and wollastonite have a specification of ≥325 mesh;

[0078] Suzhou clay, barium carbonate, zinc oxide, borax, lead oxide, iron red powder, cobalt blue powder specifications ≥ 200 mesh;

[0079] The frit is granular;

[0080] Sodium humate, styrene acrylic emulsion, silica sol and water glass are all liquids. In the process of use, the adhesion of water glass is better than that of silica sol, the adhesion of styrene acrylic emulsion is better than that of water glass, and the leveling property of silica sol is better than that of water glass and styrene acrylic emulsion. The three binders are added at the same time to complement each other and improve their comprehensive performance.

[0081] The binder is one or a mixture of silica sol, water glass or styrene acrylic emulsion.

[0082] The binder is a mixture of silica sol, water glass and styrene acrylic emulsion, and the amount of water glass added is 18% to 23%. After being kept at 800℃ for 3 hours, the glaze can form a relatively complete and smooth glaze layer on the surface of the three major parts (long nozzle, stopper rod, and immersion nozzle). When the amount of water glass added in the glaze is increased to 30% to 45%, the glaze layer is incomplete, and the surface of the three major parts (long nozzle, stopper rod, and immersion nozzle) is more exposed. The reason is that as the amount of water glass added increases, the viscosity of the glaze at 800℃ is large, and the fluidity is small, so "shrinkage" occurs.

[0083] Chromium oxide green, cobalt blue powder, and iron oxide red powder are all pigments. Chromium oxide green is green at 1100℃, cobalt blue powder is black at 1100℃, and iron oxide red is brown-red at 1100℃. The effect of colored glaze depends on the chemical composition of the base glaze, the amount of colorant added, the thickness and uniformity of the glaze, and the kiln atmosphere during firing. Black cobalt oxide is the strongest colorant in glazes. When the content is less than 1%, it can form a bright blue. Chromium oxide can make some glazes appear green, while in glazes with other ingredients, it can form red, yellow, pink or brown.

[0084] According to one aspect of the present invention, a method for preparing a composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three large pieces is provided: 18% to 20% of quartz powder, 21% to 27% of potassium feldspar, 5% to 8% of Suzhou soil, 0% to 3% of barium carbonate, 8% to 12% of glass powder, 8% to 10% of pyrophyllite, 0% to 3% of zinc oxide, 5% to 7% of borax, 0% to 2% of magnesia, 0% to 3% of chromium oxide green, 0% to 3% of cobalt blue powder, 0% to 3% of iron red powder, and 0% to 1% of chromium oxide green. ~3%, diopside 0%~5%, frit 0%~15%, wollastonite 0%~5%, lead oxide 0%~2%, calcite 0%~5%, sodium humate 0%~0.2%, binder 0%~20%, silica sol 0%~8% and styrene acrylic emulsion 0%~2% and water 20%~25% are mixed, and then 20%~25% of water in proportion to the total weight of the raw material components is added, stirred for 10~18 hours, and then aged for three days before use.

[0085] Specific steps:

[0086] 1. Ingredients: According to the three formula requirements in Table 1, take dry materials as the basis, weigh the required weight of various powders, mix them and put them into the rapid ball mill barrel, run for 2 hours, and mix them evenly.

[0087] 2. Wet ball milling: add liquid additive sodium humate and liquid binder styrene acrylic emulsion, silica sol and water glass into the barrel of the fast ball mill filled with powder, and mix and stir by ball milling according to Formula 1, Formula 2 and Formula 3 in Table 1 respectively. Grind the glaze particles by the impact and friction of the corundum balls in the ball mill. The ball milling stirring time is 10 to 18 hours, until the specification of the glaze slurry reaches 0.02% to 0.05% 350 mesh residue.

[0088] 3. Screening: Use a coarse mesh screen to separate the ball material.

[0089] 4. Iron removal: Use a magnetic bar to stir the slurry in the storage barrel to remove iron impurities, repeat several times.

[0090] 5. Aging: The glaze ages for 3 to 5 days.

[0091] 6. The glaze is now prepared and will be stored in the warehouse for future use.

[0092] Table 1: Design formula of three major composite anti-oxidation and corrosion-resistant ceramic glazes

[0093]

[0094]

[0095] The classification and performance description of the above components and raw materials in the test formula product of the invention are as follows:

[0096] 1. Lead glaze and lead-free glaze

[0097] In the lead glaze formula used in the composite anti-oxidation and corrosion-resistant ceramic glaze products of the three major continuous casting parts (long nozzle, stopper rod, immersed nozzle), the source of lead comes from lead metasilicate or lead borosilicate frit. In actual production, the typical lead metasilicate formula composition is: Seger's formula 1.00 lead oxide, 0.10 aluminum oxide, 1.89 silicon dioxide, weight ratio: lead oxide 64%, aluminum oxide 3%, silicon dioxide 33%). It can produce the lowest solubility of glaze. If the content of alkaline oxides and boron oxide is increased, the solubility of lead in the frit can be increased. In countries such as the Netherlands, there are no restrictions on lead solubility. They use low-melting or high-soluble lead silicate and lead borate frit glazes. The difference between lead glaze and lead-free glaze involves product quality issues. However, at temperatures above 1150°C, lead is obviously volatilized, and above this temperature limit, lead glaze is usually no longer used. Lead-free glaze refers to the type with a lead oxide content of less than 1% by weight. As environmental protection requirements become increasingly stringent, industries in various countries have gradually turned to the use of lead-free glazes, lead-free fluxes and lead-free pigments.

[0098] 2. Raw glaze and frit glaze

[0099] Since the raw material glaze of the three major parts of continuous casting (long nozzle, stopper rod, immersion nozzle) does not use frit, they are limited to use when the maximum firing temperature is greater than 1150℃. It can usually be used for glazing the production of hard porcelain, vitrified sanitary porcelain, stoneware, electric porcelain and various low expansion blanks. The raw material glaze contains mineral solvents, such as feldspar or Nepheline syenite , plus clay, quartz, calcium carbonate, dolomite, zinc oxide and Zirconium silicate As a common raw material. Low expansion raw material glaze is also used Petalite As a flux. Raw glaze does not have any form of glass phase. During firing, sufficient time must be passed to expel the gas from the raw material components. After the glaze is melted, a smooth glaze surface without bubbles can be obtained. Therefore, the firing time of raw glaze is longer than that of frit glaze. When the firing temperature is lower than 1150℃, frit glaze is preferably used. In addition, when using low-temperature fast firing technology, the frit content in the glaze needs to be increased accordingly.

[0100] The obtained composite antioxidant and corrosion-resistant ceramic glazes for the three major continuous casting parts (long water nozzle, stopper rod, and immersed water nozzle) of Formula 1, Formula 2, and Formula 3 have the following characteristics: appearance: water-soluble liquid; color: green for Formula 1, black for Formula 2, and red for Formula 3; properties: carrier (water-soluble); specific gravity: 1.2-1.8; viscosity: 10-20P.

[0101] The three formulas of the composite anti-oxidation and corrosion-resistant ceramic glazes for the three major parts of continuous casting (long nozzle, stopper rod, submerged nozzle) have passed the test, and their performance is shown in Table 2:

[0102] Table 2 Formula 1, Formula 2 and Formula 3

[0103] Composite anti-oxidation and corrosion-resistant ceramic glaze for the three major parts of continuous casting (long nozzle, stopper rod, submerged nozzle)

[0104]

[0105] Usage requirements: spraying, brushing, dipping are all acceptable, the thickness should be between 0.5 and 0.8 mm.

[0106] The above are only some embodiments of the present invention. It should be pointed out that for ordinary technicians in this field, other modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. Continuously casting three-piece composite anti-oxidation and corrosion-resistant ceramic glaze, characterized in that: Calculated by weight percentage, it contains the following components: quartz powder 18%, potassium feldspar 22%, Suzhou soil 6%, barium carbonate 3%, glass powder 8%, pyrophyllite 8%, zinc oxide 3%, borax 5%, magnesia 2%, cobalt blue powder 3%, frit 15%, lead oxide 2%, calcite 5%, in addition to 0.02% sodium humate, 20% water glass, 8% silica sol, 2% styrene acrylic emulsion and 25% water.

2. The composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three large parts according to claim 1 is characterized in that: Calculated by weight percentage, the quartz powder: SiO2 content 99-99.5%, Fe2O3 content ≤0.005%; The magnesia: MgO content ≥ 97%, SiO2 content ≤ 0.6%, CaO content ≤ 1.2%, Fe2O3 content ≤ 0.6%; The glass powder: physical properties, appearance of white powder, whiteness: ≥94, specific gravity: 2.7g / ml, oil absorption: 28±2.5g / 100g, Mohs hardness: 7.8, chemical composition: SiO2 content 73%, Al2O3 content 0.8%, CaO content 8%, MgO content 3%, K2O content 1.8%, Na2O content 12%; The pyrophyllite: Al2O3 content ≥ 16%, SiO2 content ≤ 75%, Fe2O3 content ≤ 1.0%; The potassium feldspar has a SiO2 content of 64%, an Al2O3 content of 18%, and a K2O content of 16%.

3. The composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three large parts according to claim 2 is characterized in that: The particle size distribution of the components is as follows: the quartz powder, potassium feldspar, glass powder, pyrophyllite, magnesia, and calcite are ≥ 325 mesh; The specifications of Suzhou soil, barium carbonate, zinc oxide, borax, lead oxide and cobalt blue powder are ≥ 200 mesh; The frit is granular; The sodium humate, styrene acrylic emulsion, silica sol and water glass are all liquid.

4. A method for preparing a composite anti-oxidation and corrosion-resistant ceramic glaze for continuous casting of three major parts, characterized in that: Prepared using the following steps: A. Ingredients: 18% quartz powder, 22% potassium feldspar, 6% Suzhou soil, 3% barium carbonate, 8% glass powder, 8% pyrophyllite, 3% zinc oxide, 5% borax, 2% magnesia, 3% cobalt blue powder, 15% frit, 2% lead oxide, 5% calcite, by weight, based on dry materials, weigh the required weight of various powders, mix them and put them into the rapid ball mill barrel, run for 2 hours, and mix them evenly; B. Wet ball milling: Add liquid additives into the barrel of the fast ball mill filled with powder: 0.02% sodium humate, 20% water glass, 8% silica sol, 2% styrene acrylic emulsion and 25% water, and mix them by ball milling. The glaze particles are finely ground by the impact and friction of the corundum balls in the ball mill. The ball milling stirring time is 10 to 18 hours, until the specification of the glaze slurry reaches 0.02% to 0.05% of the 350 mesh residue; C. Screening: Use a coarse mesh screen to separate the ball material; D. Iron removal: Use a magnetic bar to stir the slurry barrel to remove iron impurities, repeat several times; E. Aging: The glaze ages for 3 to 5 days; F. The glaze is now prepared and will be stored in the warehouse for future use.

Citation Information

Patent Citations

  • Coating material on fireproof material for continuous casting device and use method thereof

    CN103130521A

  • Strong-base corrosion-resistant ceramic glaze and preparation method thereof

    CN109279780A

  • Wear-resistant glaze for preparing sanitary ceramics and method for preparing sanitary ceramics

    CN110698067A